2011
DOI: 10.1007/s11783-011-0371-x
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of perfluorooctanoic acid by microwaveactivated persulfate: Effects of temperature, pH, and chloride ions

Abstract: Microwave-hydrothermal treatment of persistent and bioaccumulative perfluorooctanoic acid (PFOA) in water with persulfate (S 2 O 2 -8 ) has been found effective. However, applications of this process to effectively remediate PFOA pollution require a better understanding on free-radical scavenging reactions that also take place. The objectives of this study were to investigate the effects of pH (pH = 2.5, 6.6, 8.8, and 10.5), chloride concentrations (0.01-0.15 mol$L -1 ), and temperature (60°C, 90°C, and 130°C)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 30 publications
2
39
1
1
Order By: Relevance
“…The presence of other species in wastewater such as chloride, sulfate, and phosphate could reduce its oxidation efficiency. It is reported earlier [27] that chloride can react with sulfate free radicals according to the following mechanism:…”
Section: Effect Of Inorganic Anionsmentioning
confidence: 99%
“…The presence of other species in wastewater such as chloride, sulfate, and phosphate could reduce its oxidation efficiency. It is reported earlier [27] that chloride can react with sulfate free radicals according to the following mechanism:…”
Section: Effect Of Inorganic Anionsmentioning
confidence: 99%
“…The acid-catalyzation decreases with the pH increase, resulting in the reduction of degradation rate. Lee et al [27] used microwave-activated persulfate to decompose perfluorooctanoic acid (PFOA) and the maximum PFOA degradation occurred at pH 2.5. In addition, sulfate radicals generated in solutions can lead to radical interconversion reactions to produce hydroxyl radicals [21].…”
Section: Effect Of Solution Phmentioning
confidence: 99%
“…Recent studies have demonstrated that high-frequency ultrasonication (Moriwaki et al, 2005;Vecitis et al, 2008;Panchangam et al, 2009a), microwave-induced persulfate (Lee et al, 2009(Lee et al, , 2012, electrochemical method (Guan et al, 2007;Zhuo et al, 2011), and photochemical and photocatalytic methods based on 185 nm VUV or 254 nm UV (Chen et al, 2007;Cho, 2011;Giri et al, 2011aGiri et al, , 2011bGiri et al, , 2012Li et al, 2012;PhanThi et al, 2013;Hori et al, 2004Hori et al, , 2005Dillert et al, 2007;Wang et al, 2008;Wang and Zhang, 2011;Panchangam et al, 2009b;Huang et al, 2007;Park et al, 2009) can degrade PFOA in a stepwise way. In oxidative processes, generally an electron transfers from PFOA to some excited active species, such as sulfate radical anion (SO 4 U− ) (Lee et al, 2009;Hori et al, 2005), carbonate radical anions (CO 3 U− ) (PhanThi et al, 2013), photogenerated holes (Li et al, 2012;Panchangam et al, 2009b) and PFOA complexes (Wang et al, 2008;Wang and Zhang, 2011), and then a perfluoroalkyl radical is formed after decarboxylation of PFOA.…”
Section: Introductionmentioning
confidence: 99%